1987
DOI: 10.1016/0005-2736(87)90156-8
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between the dual specificity of the bovine brain phosphatidylinositol transfer protein and membrane phosphatidylinositol levels

Abstract: The phosphatidylinositol transfer protein from bovine brain has a remarkable specificity pattern with a distinct preference for phosphatidylinositol (PI) and a low affinity for phosphatidylcholine (PC). In this study we have determined the affinity of Pl-transfer protein for PI relative to that for PC by measuring the binding of the fluorescent pyrene-labeled analogs of these phospholipids. From competition binding experiments it was estimated that the transfer protein has a 16-fold higher affinity for PI than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…This was clearly shown for PI-TPR, as the stability of the PG-and PI-containing complex was much higher than that of PC/ PI-TPR. In earlier experiments, the phospholipid specificity of PI-TPR was determined by a phospholipid transfer assay (4,6,32,33) or by a competition binding assay (28,34). From these studies, it was gathered that PI-TPR binds PI about 16-fold better than PC or PG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was clearly shown for PI-TPR, as the stability of the PG-and PI-containing complex was much higher than that of PC/ PI-TPR. In earlier experiments, the phospholipid specificity of PI-TPR was determined by a phospholipid transfer assay (4,6,32,33) or by a competition binding assay (28,34). From these studies, it was gathered that PI-TPR binds PI about 16-fold better than PC or PG.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the voltage to 120 V showed that the dissociation between PG and PI-TPR, as apparent from the appearance The present measurements do not allow one to distinguish between these two residues, but do reveal that the noncovalent interaction between PG and PI-TPR in the gas phase is very strong and approaches that of a peptide bond. Since PI-TPR from mammalian cells carries either a PI or a PC molecule (5,27,28), we have analyzed these complexes as well. As shown in Figure 5, PI and PG dissociated from PI-TPR at a relatively high cv, whereas PC dissociated at a cv comparable to that observed for the PC/PC-TP complex.…”
Section: Esi-tof Analysis Of the Phosphatidylcholine Transfermentioning
confidence: 99%
“…The difference between optimally bound and poorly bound (transferred) species is larger for PC than for PI. This may be due to the fact that the binding affinity is also dependent on the phospholipid head groupprotein interactions, which are approximately 15-fold stronger for PI than for PC (Van Paridon et al, 1987b). In other words, the fractional contribution of the acyl chains to the binding affinity could be much larger in the case of PC.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this the gene of human PI-TPa is localized to chromosome 17q13 and of PI-TPb to chromosome 22q12 (Ocaka et al, 2005). Both isoforms act as carriers of PI and phosphatidylcholine (PC) between membranes in vitro, yet PI-TPb can also transfer sphingomyelin (SPM) (Van Paridon et al, 1987b;De Vries et al, 1995). At this point it is still questionable whether these proteins actually transfer these phospholipids between membranes within cells or whether they interact directly with enzymes like PI 4-kinases and PI-specific phospholipase A 2 thereby providing these enzymes with substrates Snoek et al, 1999).…”
Section: Introductionmentioning
confidence: 58%
“…A main feature of PI-TPa is its dual specificity expressing a 16-fold higher affinity for PI than for PC (van Paridon et al, 1987b). Recently, the structures of rat PI-TPa carrying a PC molecule and of human PI-TPa carrying a PI molecule were elucidated (Yoder et al, 2001;Tilley et al, 2004) (Fig.…”
Section: D-structure and Phospholipid Specificity Pi-tpamentioning
confidence: 99%